An Analysis of Students Responses on Mathematics Learning Based on Google Classroom - Tetty Natalia Sipayung; Imelda Imelda; Tatag Yuli Eko Siswono; Masriyah Masriyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
A teacher needs to observe student responses when learning takes place. During the Covid- 19 pandemic, it was to observe student responses when learning takes place online. However, efforts are still being made to determine student responses to online learning. Student responses is needed to determine the cognitive and affective development of student when learning take place. Therefore, a study was conducted on the analysis of student responses to mathematics learning. Mathematics learning applied in this study uses online learning, namely using a learning container, namely Google Classroom. This research ia a qualitative research which aims to analyze students’ responses to mathematics learning based on google classroom. This research involved subjects, namely students of class VII-C SMP Santo Yoseph Medan in the odd semester of the 2020/2021 Academic Year, totaling 32 people. The instrument used to analyze student responses was a questionnaire designed online in the form of a google form. The results of this study explain that student responses are positive towards google classroom-based mathematics learning. This is studied based on indicators of student responses.